Green colonialism in the European Green Deal: Continuities of dependency and the relationship of forces between Europe and Africa - Simone Claar (Culture, Practice & Europeanization)
In 2019, the European Union set a new course for a sustainable Europe with the European Green Deal (EGD), which included not only energy strategies but also mobility or clean water for a green Europe. The European Green Deal policies have implications and global effects on other world regions, e.g., the African continent. As I would argue, the EGD has a new EU-Africa strategy, which is marked by a continuity of dependency and might be an enabler of green colonialism. Existing patterns of dependency between Africa and Europe are reproduced, but new demands are made vis-à-vis African states which are supposed to implement European ecological transformation plans. This article discusses two fields of the EU-Africa strategy in the EGD: hydrogen and biodiversity. It shows that the EGD preserves the existing asymmetric relationship between Africa and the EU by highlighting the elements of green capitalism and green colonialism. Furthermore, it discusses alternative socio-ecological transformation methods in Africa, e.g., the South African Climate Justice Charter.